Klemann's transnational turn and petropreneurship in the port of Rotterdam, 1860-2000s - Boon, Marten (Sidestone Press, 2025)
This paper provides a sketch of the origins and fates as well as the similarities and differences between phases of petropreneurship in the Port of Rotterdam. In doing so, it aims to illustrate the implications of, what I call, Hein Klemann’s transnational turn for writing the economic and business history of port cities. Through a study of local entrepreneurs in petroleum, the interconnected nature of the local, regional and global is highlighted, showcasing the strong rationale of employing a transnational perspective. Using examples from 150 years of local petropreneurship in the port of Rotterdam, I argue that the fates of these petropreneurs have always been bound up with larger shifts in industry structure, technology and geopolitics and that a transnational perspective is therefore indispensable to understand the history of ports and their entrepreneurs.